Author Correction: Transplanted miR-219-overexpressing oligodendrocyte precursor cells promoted remyelination and improved functional recovery in a chronic demyelinated model. Issue 1 (December 2018) - Fan, Hong-Bin; Chen, Li-Xia; Qu, Xue-Bin; Ren, Chuan-Lu; Wu, Xiu-Xiang; Dong, Fu-Xing; Zhang, Bao-Le; Gao, Dian-Shuai; Yao, Rui-Qin
A correction has been published and is appended to both the HTML and PDF versions of this paper. The error has not been fixed in the paper.